The antimicrobial efficacy of siwak (Salvadora persica) extract towards Streptococcus sanguis - Bohari, Nurul Iradah; Hardjawinata, Karlina; Sudjarwo, Indrati (Padjadjaran Journal of Dentistry, 2010)
Introduction: Siwak (Salvadora persica) has been used for good oral hygiene maintenance purposes by the Babylonians since 7000 years ago and also by the Greek, Roman, Egyptian, and Arabian. The aim of this study is to assess the antimicrobial efficacy of siwak extract towards Streptococcus sanguis as the oral-plaque-inducer, by determining the Minimum Inhibitory Concentration (MIC) and exposure time, to determine whether siwak extract could be chosen as an alternative ingredient for plaque control. Methods: Type of research is experimental laboratory. The MIC test were conducted based on a serial dilution of 64%, 32%, 16%, 8%, 4%, 2%, 1%, 0.5%, 0.25%, and 0.125% concentration of siwak extract respectively, against 5 samples of Streptococcus sanguis within three repetitions. The exposure time test has been performed within 30 seconds, 1’, 2’, 3’, and 4’ with 0.25%, 0.5%, and 1.0% concentration of siwak extract. Results: The siwak extract can inhibit Streptococcus sanguis at the concentration of 0.25% to 0.125%. There is no antimicrobial effect towards Streptococcus sanguis until 4 minutes of exposure time. Conclusion: Siwak extract had the antimicrobial effect towards Streptococcus sanguis in minimum concentration between 0.25% - 0.125% with the exposure time more than 4 minutes.